Avoiding Theoretical Stagnation: A Systematic Review and Framework for Measuring Public Value. Issue 1 (18th May 2017) - Faulkner, Nicholas; Kaufman, Stefan
Abstract: Public value theory has become a hot topic in public administration research, but its proponents have long recognised difficulties in empirically testing the theory's central propositions. There has been a lack of clarity about how to measure the extent to which organisations are generating public value, which has rendered researchers unable to quantitatively study the causes, consequences and correlates of public value. The current study systematically reviews the growing literature on public value measurement to identify, evaluate, and synthesise available measures. Through a qualitative synthesis of the themes present in published measures, we identify four key components for measuring public value that appear to be important across a range of policy and national contexts. Our review identifies a promising framework that could be used to structure a comprehensive measure of public value and, in doing so, provides a means to progress theoretical development and testing of the public value approach. Abstract : Despite its popularity, many of the central tenets of public value theory remain untested due to a lack of clarity on how to measure public value. In this article, we systematically review research on public value measurement and synthesise a general framework for structuring measures of public value.